Inkerikot, setot ja vatjalaiset : Kansankulttuuri, kieli ja uskomusperinteet - Kallio, Kati (2022)
The book focuses on intangible and tangible heritage, language, and vernacular religion of Ingrians, Setos, and Votes, three Finnic minorities sharing the long-standing identification with the Orthodox faith. The chapters written by 16 authors are mainly based on 19th–20th century materials. Most rely on archival sources, while some authors make use of their own fieldworks. The research history and the collecting of folklore materials are discussed as well. The historical area of Ingrians and Votes is located in Ingria adjacent to St. Peterburg, while Setos have inhabited both sides of southern Estonian–Russian border. All three groups have been living on the borderline of Eastern and Western Churches and cultural realms. Ingrians and Votes are the indigenous inhabitants of Ingria, while the secondarily gained Ingrian-Finn population speaks local varieties of Finnish. The Finnish settlements mostly arose during the 17th century as a consequence of the expanding Swedish Kingdom. To a large extent, the Seto language and South Estonian Võru dialect are linguistically identical, but the Setos are culturally and ethnically clearly distinct. Currently, the Ingrian and Votic language are extremely endangered, while Seto language has approximately 12 000 speakers. There is a high local interest towards maintenance and revitalization of all three languages and cultural traditions. Peer reviewed